2015
DOI: 10.1093/aje/kwu316
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of the Association Between Low Socioeconomic Status and Chronic Kidney Disease in the United States

Abstract: Using data collected from 9,823 participants in the 2007-2008 and 2009-2010 cycles of the National Health and Nutrition Examination Survey, we formally investigated potentially modifiable factors linking low socioeconomic status (SES) to chronic kidney disease (CKD) for their presence and magnitude of mediation. SES was defined using the poverty income ratio. The main outcome was CKD, defined as estimated glomerular filtration rate <60 mL/minute/1.73 m(2) (using the Chronic Kidney Disease Epidemiology Collabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 56 publications
2
60
0
Order By: Relevance
“…24 Mediators of low cosioeconomic status and CKD prevalence appear to be related to modifiable risk factors such as smoking, alcohol use, diet, and physical activity, which are reported to contribute 20% of risk variance, while comorbid conditions contribute 30%, and access to care 11%. 25 The current study found that education was a potent predicator of rapid kidney function decline, while income and access to care trended towards an association.…”
Section: Discussionmentioning
confidence: 59%
“…24 Mediators of low cosioeconomic status and CKD prevalence appear to be related to modifiable risk factors such as smoking, alcohol use, diet, and physical activity, which are reported to contribute 20% of risk variance, while comorbid conditions contribute 30%, and access to care 11%. 25 The current study found that education was a potent predicator of rapid kidney function decline, while income and access to care trended towards an association.…”
Section: Discussionmentioning
confidence: 59%
“…Many of these factors are complex and varied, and a large number of interrelated factors likely contribute. Work from the USA among people with chronic kidney disease has reported potentially modifiable factors such as health‐related behaviours (smoking, alcohol and physical activity), co‐morbid conditions and healthcare access (health insurance and health visits) substantially explain the association between SES and chronic kidney disease . Determining future actions to reduce the gap needs further work.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, many people with low SES have an unhealthy lifestyle [21] [23] [24]. Priya et al showed that proportion of participants with unhealthy lifestyles, such as high alcohol intake and physical inactivity were higher in participants with low SES [25]. It may be that metabolic risks, such as DM, DL, HT and obesity, in addition to unhealthy lifestyle factors, are mediators of the association between low SES and CKD [25].…”
Section: Discussionmentioning
confidence: 99%
“…Priya et al showed that proportion of participants with unhealthy lifestyles, such as high alcohol intake and physical inactivity were higher in participants with low SES [25]. It may be that metabolic risks, such as DM, DL, HT and obesity, in addition to unhealthy lifestyle factors, are mediators of the association between low SES and CKD [25]. In summary, unhealthy lifestyles and metabolic risk factors may develop due to low SES, resulting in CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation